K niektorým aspektom vymedzenia pojmov etnicita: Národ a úlohy etnicity v procese formovania novodobých národov - Olejník, Milan (Lidé města, 2003)
The notions of nationality and ethnicity stubbornly resists attempts to define them with scientific, or at least, comfortable degree of precision. Vagueness and versatility of these notions are consequently affecting characterization of their mutual relation and their role in history of humankind. This vagueness is strikingly noticeable when historical sociological, ethnographical and other analysis of these notions is attempted. ln spite of almost ephemeral nature of ethnicity and rationality, their significance in modern history is staggering. The paper is offering, in concise mode , an overview of basic approaches to these issues by diverse authors in general level and is attempting to implement theoretical outcomes to the concrete conditions, which had an impact upon the history of Slovakia.